Worship sound spaces: architecture, acoustics and anthropology - Guillebaud, Christine; Lavandier, Catherine (Routledge, 2020)
"Worship Sound Spaces unites specialists from architecture, acoustic engineering and the social sciences to encourage closer analysis of the sound environments within places of worship. Gathering a wide range of case studies set in Europe, Asia, North America, the Middle East, and Africa, the book presents investigations into Muslim, Christian and Hindu spaces. These diverse cultural contexts demonstrate the composite nature of designing and experiencing places of worship. Beginning with a historical overview of the three primary indicators in acoustic design of religious buildings, reverberation, intelligibility and clarity, the second part of this edited collection offers a series of field studies devoted to perception, before moving onto recent examples of restoration of the sound ambiances of former religious buildings. Written for academics and students interested in architecture, cultural heritage, acoustics, sensory studies and sound"--
Includes bibliographical references and index
"This book is based on the work that was conducted at the International Conference Worship Sojnd Spaces, ..., held in Paris at the Musée du quai Branly-Jacques Chirac." - Acknowledgments
Keywords: Konferenzschrift -- 2015 -- Paris; Raumakustik; Akustik; Sakralbau